5. EVALUATING THE EFFICACY OF COMBINED FUROSEMIDE AND ALBUMIN THERAPY DURING THE EVACUATION PHASE IN SEPTIC SHOCK PATIENTS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the efficacy of combining Furosemide and Albumin versus Furosemide alone during the evacuation phase in patients with septic shock.Materials and methods: A prospective, randomized controlled trial was conducted on 44 patients with septic shock during the fluid evacuation phase, admitted to the Anesthesia and Surgical Intensive Care Center, Viet Duc University Hospital from January to June 2025. Patients were randomly assigned to two groups: group 1 received Furosemide in combination with Albumin, while group 2 received Furosemide alone. Parameters assessed over 24 hours post-intervention included urine output, fluid balance, PaO2/FiO2 ratio, and hemodynamic variables.Results: Group 1 demonstrated significantly higher mean urine output compared to Group 2 (4532.73 ± 946.14 ml vs. 3781.82 ± 925.63 ml; p = 0.011), a more negative fluid balance (p = 0.015), and a higher proportion of patients achieving negative fluid balance (100% vs. 72.7%; p = 0.021). Improvement in PaO2/FiO2 was also significantly greater in group 1 (p < 0.001). The incidence of hypotension was lower in group 1 (9.1% vs. 18.2%), though the difference was not statistically significant.Conclusion: The combination of Furosemide and Albumin during the evacuation phase increases urine output, promotes negative fluid balance, improves gas exchange, and reduces the incidence of hypotension compared to Furosemide alone in patients with septic shock.